Quilting modern : techniques and projects for improvisational quilts - Gering, Jacquie (Interweave Press, 2012)
"From two pioneers of today's modern quilting movement, Quilting Modern teaches quilters how to use improvisational techniques to make graphic, contemporary quilts and quilted projects. Explore seven core techniques and multiple projects using each technique-all presented with detailed instructions. Also included is step-by-step direction from Jacquie Gering and Katie Pedersen on tools, materials, and quilting basics, as well as expert advice on color and design. New and seasoned quilting artists will love making stunning bed, wall hanging, pillowcase, and table accessory quilts with this must-have resource. Quilting Modern is a field guide for quilters who strive to break free from tradition and yearn to explore improvisational work. Quilters can make the 21 projects in the book, but will also come away with the new knowledge and skills to apply to their own unique designs. In Quilting Modern, quilters will find the support, structure, and encouragement they need to explore their own creativity and artistic vision."--